Neopopulism in Colombia: Case of the government of Álvaro Uribe Vélez - Galindo Hernández, Carolina (2007)
This article develops an analysis on the stregthening process in the administrative branch of government in Colombia during the administration of President Álvaro Uribe Vélez. This analysis is done within the context of similar processes evolving recently in the Andean Region. This context shows a sort of disenchantment of the democratic system among wide sectors of society, represented in ways of politically aiming at patterns which seem to reproduce old governing schemas like neopopulism, the coming back of old authoritarian patterns and the leadership of outsiders. Considering this background, this article intends to establish if the governing program of the present president of Colombia, Álvaro Uribe actually adjusts to the neopopulist line, analyzing at the same time the limitations of the use of the term neopopulism in explaining actual political Colombian experience.